Pengaruh Lingkungan Belajar, Fasilitas Belajar, dan Stres Akademik Terhadap Motivasi Belajar Mahasiswa Fakultas Ekonomi Universitas Negeri Jakarta - Fakhira Sabrina Mukitasari; Christian Wiradendi Wolor; Marsofiyati Marsofiyati (Jurnal Multidisiplin Indonesia, 2023)
This research aims to determine whether there is a positive and significant influence between the learning environment, learning facilities, and academic stress on student learning motivation. This research was conducted at the State University of Jakarta which is located at Jl. Rawamangun Muka, RT.11 / RW.14, Rawamangun, Pulo Gadung, East Jakarta City, Special Capital Region of Jakarta 13220. The population used in this study were students of the Faculty of Economics, State University of Jakarta, with a sample size of 100 people. The research method used is the quantitative method. The data obtained is primary data through survey data collection methods. Data collection using a questionnaire or questionnaire through the Google Form platform which is distributed online. The data analysis technique used in this study is the Structural Equation Model (SEM) using the Smart PLS 4.0 software application.